Protein Bioinformatics Applied to Virology - Mohabatkar, Hassan; Keyhanfar, Mehrnaz; Behbahani, Mandana (Current Protein and Peptide Science, 2012)
Scientists have united in a common search to sequence, store and analyze genes and proteins. In this regard, rapidly evolving bioinformatics methods are providing valuable information on these newly-discovered molecules. Understanding what has been done and what we can do in silico is essential in designing new experiments. The unbalanced situation between sequence-known proteins and attribute-known proteins, has called for developing computational methods or high-throughput automated tools for fast and reliably predicting or identifying various characteristics of uncharacterized proteins. Taking into consideration the role of viruses in causing diseases and their use in biotechnology, the present review describes the application of protein bioinformatics in virology. Therefore, a number of important features of viral proteins like epitope prediction, protein docking, subcellular localization, viral protease cleavage sites and computer based comparison of their aspects have been discussed. This paper also describes several tools, principally developed for viral bioinformatics. Prediction of viral protein features and learning the advances in this field can help basic understanding of the relationship between a virus and its host.
Keywords: protein docking